Whole-transcriptome analyses identify key differentially expressed mRNAs, lncRNAs, and miRNAs associated with male sterility in watermelon - Yue, Zhen; Pan, Xiaona; Li, Jiayue; Si, Fengfei; Yin, Lijuan; Hou, Yinjie; Chen, Xiaoyao; Li, Xin; Zhang, Yong; Ma, Jianxiang; Yang, Jianqiang; Li, Hao; et al. (Frontiers in Plant Science, 2023)
Male sterility is a valuable trait for watermelon breeding, as watermelon hybrids exhibit obvious heterosis. However, the underlying regulatory mechanism is still largely unknown, especially regarding the related non-coding genes. In the present study, approximately 1035 differentially expressed genes (DEGs), as well as 80 DE-lncRNAs and 10 DE-miRNAs, were identified, with the overwhelming majority down-regulated in male-sterile floral buds. Enrichment analyses revealed that the general phenylpropanoid pathway as well as its related metabolisms was predicted to be altered in a mutant compared to its fertile progenitor. Meanwhile, the conserved genetic pathway DYT1-TDF1-AMS-MS188-MS1, as well as the causal gene ClAMT1 for the male-sterile mutant Se18, was substantially disrupted during male reproductive development. In addition, some targets of the key regulators AMS and MS188 in tapetum development were also down-regulated at a transcriptional level, such as ABCG26 (Cla004479), ACOS5 (Cla022956), CYP703A2 (Cla021151), PKSA (Cla021099), and TKPR1 (Cla002563). Considering lncRNAs may act as functional endogenous target mimics of miRNAs, competitive endogenous RNA networks were subsequently constructed, with the most complex one containing three DE-miRNAs, two DE-lncRNAs, and 21 DEGs. Collectively, these findings not only contribute to a better understanding of genetic regulatory networks underlying male sterility in watermelon, but also provide valuable candidates for future research.